Cost of nursing turnover in a Teaching Hospital - Ruiz,Paula Buck de Oliveira (2016)
Abstract OBJECTIVE To map the sub processes related to turnover of nursing staff and to investigate and measure the nursing turnover cost. METHOD This is a descriptive-exploratory study, classified as case study, conducted in a teaching hospital in the southeastern, Brazil, in the period from May to November 2013. The population was composed by the nursing staff, using Nursing Turnover Cost Calculation Methodology. RESULTS The total cost of turnover was R$314.605,62, and ranged from R$2.221,42 to R$3.073,23 per employee. The costs of pre-hire totaled R$101.004,60 (32,1%), and the hiring process consumed R$92.743,60 (91.8%) The costs of post-hire totaled R$213.601,02 (67,9%), for the sub process decreased productivity, R$199.982,40 (93.6%). CONCLUSION The study identified the importance of managing the cost of staff turnover and the financial impact of the cost of the employee termination, which represented three times the average salary of the nursing staff.